2007
DOI: 10.1007/s10652-006-9016-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis of Froude number effect on air entrainment in the hydraulic jump

Abstract: A hydraulic jump is characterized by strong energy dissipation and mixing, large-scale turbulence, air entrainment, waves, and spray. Despite recent pertinent studies, the interaction between air bubbles diffusion and momentum transfer is not completely understood. The objective of this paper is to present experimental results from new measurements performed in a rectangular horizontal flume with partially developed inflow conditions. The vertical distributions of the void fraction and the air bubbles count ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 13 publications
(31 reference statements)
1
28
0
1
Order By: Relevance
“…Bubbly two-phase flow in a hydraulic jump using a flow visualization technigue were studied by Mossa and Tolve [12]. The air-water flow properties in a hydraulic jump were extensively studied Gualtieri and Chanson [13], Chanson and Gualtieri [14], Gualtieri and Chanson [15] and Gualtieri and Chanson [16].…”
Section: Introductionmentioning
confidence: 99%
“…Bubbly two-phase flow in a hydraulic jump using a flow visualization technigue were studied by Mossa and Tolve [12]. The air-water flow properties in a hydraulic jump were extensively studied Gualtieri and Chanson [13], Chanson and Gualtieri [14], Gualtieri and Chanson [15] and Gualtieri and Chanson [16].…”
Section: Introductionmentioning
confidence: 99%
“…In plunging jet and hydraulic jumps, such large-scale vortices are generated in the developing shear layers. As the vortical, coherent structures are advected downstream, they grow up in size by vortex pairing and contribute to further clustering (Gualtieri and Chanson 2007a). (Table 1).…”
Section: Clustering Analysis: Criteria Results and Discussionmentioning
confidence: 99%
“…The vertical probe position was adjusted by 0.1 mm increments. The experiments yielded the void fraction C and the bubble count rate F over the depth at various distances from the jump toe on the channel centreline (Gualtieri and Chanson 2007a). The air concentration or void fraction C is the proportion of time during which the probe tip is in air, whereas the bubble count rate F ¼ number of bubbles impacting the probe tip per second.…”
Section: Experimental Set-up: Channel and Instrumentationmentioning
confidence: 99%
“…The air entry will depend on different variables, as the upstream Froude number of the jet (Kalinske & Robertson, 1943), jet velocity (Kenn & Zanker, 1967), the recirculating vortex (Goldring et al, 1980), the surface roughness of the jet (Ervine et al, 1980). Chanson (1995) , Chanson & Gualtieri (2008), and Gualtieri & Chanson (2007) noted that viscous and surface tension effects are important for air entrainment of hydraulic jumps. Pothof & Clemens (2010), Pothof & Clemens (2011) found that the air transport for various flow regimes depends on the water flow number, pipe slope, and surface tension.…”
Section: Air Entrainmentmentioning
confidence: 99%